Characteristics of sediment in the intertidal zone of the west coast waters of Aceh Besar - Fitriah Nanda; Irham Muhammad; Dewiyanti Irma (BIO Web of Conferences)
Aceh Besar west coast is one of the beaches on the west coast of Aceh Besar Regency located in Aceh Province, the tip of Sumatra Island, Indonesia. In the intertidal zone of the west coast there are many human activities such as tourism, industry, and fisheries. The purpose of this study is to determine the characteristics of sediments including the physical and chemical of sediments in the intertidal zone of the west coast of Aceh Besar. The method used in this study is a survey method, which is carried out in the field directly to collect the data and samples. Samples were analyzed in the laboratory to determine the texture of sediment and its percentage. Sediment texture found in the intertidal zone of the west coast of Aceh Besar are sand and sandy loam. The sediment fraction is dominated by the sand fraction with a percentage of 81-90%. The content of organic carbon in the sediment is in the low category. The salinity value of the sediment shows high salinity results and the pH value of the sediment in the intertidal zone shows an alkaline pH category at each research station.